1 - Public Sphere, Linguistic Sphericules and Discourse Communities in Africa - Ambadiang Théophile (Africa Development, 2021)
Discourse, as seen in Habermas’s definition of the public sphere, is an essential aspect of the participation of the citizenry in the public debate which, crucially, is supposed to take place in a linguistically homogeneous society. The aim of this paper is to discuss the centrality of discourse in Habermas’s theory in a genuinely multilingual context as is sub-Saharan Africa. We intend to show that the discursive practices and, more generally, the complex dynamics that characterize public debate in this context are determined by sociolinguistic factors such as ‘elite closure’, linguistic repertoire, as well as by social exclusion (Scotton 1993). Elite closure, considered as social exclusion based on linguistic competence, has had the effect of constructing a public sphere around a specific version of the European (official) language, as it excludes the majority of the citizenry who makes use of the popular versions of these languages. The correlation that exists between visibility (in the public sphere) and register repertoire accounts for the uniformity or homogeneity in the register that tends to characterize public debates, as even individuals who typically use the popular versions of the European languages adopt the register of the elite (often with undesired effects). Language, thus, divides the public sphere in smaller groups along the lines of register competence as well as of linguistic competence which excludes those who have no knowledge of the European official language. This study further suggests that those groups or sphericules (Gitlin 1998) constitute discourse communities in the sense of Watts (1999), that is, sets of individuals whose discourse practices reveal common interests, goals and beliefs. Lastly, we argue that the visibility of all such groups requires the openness of the public sphere to diverse discourses (Fairclough 1999, 2006), independently of the way they materialize. In this sense, the contribution of the individuals whose linguistic repertoires do no include European languages will not necessarily nor exclusively be framed in linguistic terms. One interesting consequence of the discussion is the disempowering/disempowerment of the (European) languages in the African public sphere.